Hebermas' models of decisionism, technocracy and pragmatism in times of governance: the relationship of public administration, politics and science in the alcohol prevention policies of the Swiss member states - Sager, Fritz (2007)
This article assesses the effects different constellations of science, administration and the political sphere display on the policy process in the field of alcohol prevention policy in the Swiss member states. First, it is argued that Habermas' modes of Decisionism, Technocracy, and Pragmatism can be interpreted as distinct modes of governance that take place in today's policy-making and implementation. Second, as for the effects of these different constellations of science, administration and politics, the findings from a written survey of the Swiss cantons reported here imply that a broad and adequate policy design is found in cantons with an alcohol prevention policy that is dominated by administrative actors. Output performance proves to be comparatively higher in cantons with a high influence either of scientific actors or of political actors. In an overall comparison, a combined model of administrative dominance with strong affiliation to the scientific community is shown to prevail against the other models considered. - Reproduced.
Keywords: Public administration